The Effect of Customer Satisfaction on Loyalty: A Moderating Role of Corporate Communication in the Banking Sector - Mishra, U. (The Journal of Knowledge and Innovation, 2022)
In the 21st global competitive arena, the ultimate objective of any institution is to transform satisfied customers into loyal customers. Customer loyalty is highly affected by the satisfaction they obtain out of any service. Therefore, it is crucial to understand the relationship between customer satisfaction and customer loyalty. This study aims to examine the effect of customer satisfaction on customer loyalty with the mediating role of corporate communication. To collect data for the study, a convenience sampling method was used and 275 customers from different banks in Biratnagar participated in the survey. Structural equation modeling (SEM) was used to test the proposed hypothesis. The results depict that customer satisfaction positively and significantly associates with customer loyalty and this association is also strongly mediated by corporate communication. Moreover, corporate communication has a direct and positive influence on customer loyalty. This study has theoretical implications as it provides a better understanding of the relationship between satisfaction and loyalty.